Menelisik Kepastian Hukum Akta Wasiat atas Pencairan Deposito Pewaris yang Ditahan oleh Bank - Alghaffar, Anandito Fadli; Sri Marniati, Felicitas; Sailellah, Sirajudin (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2025)
A will serves as strong evidence in the event of a legal dispute in court and is regulated under Article 875 of the Civil Code. A will may include instructions regarding the provision of a deposit. In cases where a beneficiary, designated as an heir according to the testament, seeks to withdraw the deposit from the Bank, the Bank may withhold it, raising issues regarding the legal consequences of such withholding and the assurance of legal certainty concerning the beneficiary’s right to withdraw the deposit under the will. To address these issues, the researcher applied the theory of Legal Consequences by R. Soeroso and the theory of Legal Certainty by John Michiel Otto. The study employed a normative juridical research method, using library research and secondary data obtained from primary, secondary, and tertiary legal sources. The research approach included statutory, conceptual, analytical, and case-based analyses. Legal data were collected through identification and inventory of applicable laws, books, journals, and other relevant legal references, and were analyzed using grammatical interpretation, analogy, and legal reasoning. The research findings reveal that legal consequences arise when the Bank withholds the deposit. While the legal relationship between the testator and the Bank terminates, the beneficiary acquires rights and obligations upon the disbursement of the deposit. Furthermore, legal certainty is achieved through court decisions, which ensure the enforceability of the will and the beneficiary’s right to access the deposit.